Development Of Picture And Letter Poster Media To Improve The Ability To Recognize Pictures And Letters In Young Children - Nana Maryana; Alfauzan Amin (Journal of Research in Social Science and Humanities, 2025)
Produce flannel letter board media for early childhood, animal themes  to  improve  the  language  skils  of  early  childhood  group  B  in  TKK  Salvatoris Satap SDI Soka, South Golewa District.  Ngada Regency, (2) knows the quality of the results  of  the  flannel  letter  board  media  product  trials  on  animal  themes  for  early childhood group A at TKK  Salvatoris Satap SDI Soka. This letter flannel board media was  developed  with  the  ADDIE  model.  This  model  consists  of  five  parts,  namely:  (1) analize,  (2)  design,  (3)  development,  (4)  implementation,  and  (5)  evaluation. Theresults  of  research  on  the  development  of  letter  flannel  board  media  based  on  the results of expert trials and early childhood as product users are as follows: (1) media expert trials are in the valid category, (2) material expert trials are categorized as very valid,  (3)  expert  design  trials  with  valid  categories,  (4)  small  group  trials  with  valid categories, (5) individual trials with very valid categories. Thus, based on the results of the flannel board media trial results for AUD by experts that it is feasible to use in the learning